2016
DOI: 10.18632/oncotarget.13201
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 induces invasion and the epithelial-mesenchymal transition in human gastric cancer cells via non-canonical activation of the hedgehog signaling pathway

Abstract: Galectin-1 (Gal-1) has been reported to be an independent prognostic indicator of poor survival in gastric cancer and overexpression of Gal-1 enhances the invasiveness of gastric cancer cells. However, the downstream mechanisms by which Gal-1 promotes invasion remains unclear. Moreover, the function of Gal-1 in the epithelial-mesenchymal transition (EMT) in gastric cancer has not yet been elucidated. In this study, we observed Gal-1 expression was upregulated and positively associated with metastasis and EMT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…In the present study, we observed that in tumor tissue samples from 127 patients with GC samples, Gal-1 is overexpressed in human GC as compared with matched nontumor tissues, which consistent with previous reports [18,34] . We also confirmed that expression of S1PR1 in human GC tissue was higher than in matched non-tumor tissue, and that expression of Gal-1 was positively correlated with S1PR1 expression in GC tissue.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we observed that in tumor tissue samples from 127 patients with GC samples, Gal-1 is overexpressed in human GC as compared with matched nontumor tissues, which consistent with previous reports [18,34] . We also confirmed that expression of S1PR1 in human GC tissue was higher than in matched non-tumor tissue, and that expression of Gal-1 was positively correlated with S1PR1 expression in GC tissue.…”
Section: Discussionsupporting
confidence: 93%
“…It could regulate apoptosis and cell differentiation, bind with CD45, CD3 and CD4 to inhibit CD45 protein phosphatase activity and lymphocyte-activated enzyme dephosphorylation [25]. Studies confirmed that Gal-1 was closely related with tumor development, metastasis, invasion and malignancy, such as gastric cancer [26], ovarian cancer [27], and pancreatic cancer [28]. In this study, our data indicated that Gal1 could promote CRC cells proliferation, migration and invasion.…”
Section: Discussionsupporting
confidence: 54%
“…EMT is an important process in carcinogenesis since it increases the invasive ability of cancer cells (26,27). As a result of EMT, epithelial-derived tumor cells lose their features and obtain mesenchymal-like characteristics (28,29), and tumor cells invade the surrounding tissue and break through the capillary into the circulatory system, leading to distant metastasis (30).…”
Section: Discussionmentioning
confidence: 99%